Chemoselective N-acetylation of primary aliphatic amines promoted by pivalic or acetic acid using ethyl acetate as an acetyl donor. Issue 12 (22nd March 2017) - Yoshida, Tomoki; Kawamura, Shimpei; Nakata, Kenya
Graphical abstract: Highlights: A chemoselective N-acetylation of primary aliphatic amines was achieved. Ethyl acetate was used as an acetyl donor. This method is very simple and convenient for the preparation of acetamides. Abstract: The combination of pivalic or acetic acid as a promoter and EtOAc as a solvent and acetyl donor proved to be efficient for the chemoselective N-acetylation of primary aliphatic amines to afford the corresponding acetamides. We developed a simple and convenient approach, which requires mild reaction conditions. Competitive inter- and intramolecular reactions between aliphatic amines, alcohols, and aromatic amines were examined, and chemoselectivity was achieved by adjusting the conditions of the reaction.